The THINC-it Tool for Cognitive Assessment and Measurement in Major Depressive Disorder: Sensitivity to Change - McIntyre, Roger S.; Subramaniapillai, Mehala; Park, Caroline; Zuckerman, Hannah; Cao, Bing; Lee, Yena; Iacobucci, Michelle; Nasri, Flora; Fus, Dominika; Bowie, Christopher R.; Tran, Tanya; Rosenblat, Joshua D.; et al. (Frontiers in Psychiatry, 2020)
Background: Herein, we sought to determine the sensitivity to change in cognitive function, as measured by the THINC-it tool, in a sample of adults with major depressive disorder, receiving standardized antidepressant therapy. Methods: Adults meeting DSM-5 criteria for MDD with at least moderate depressive symptom severity [i.e., Montgomery Åsberg Depression Rating Scale (MADRS) total score ≥20] treated with open-label vortioxetine (10-20 mg/day, flexibly-dosed) for 8 weeks. The previously validated THINC-it tool was the primary dependent measure. The THINC-it tool was validated against the paper and pencil version of the Digit Symbol Substitution Test (DSST) and the Trails Making Test B (TMTB) Results: After 8 weeks of treatment, adults with MDD exhibited improvement in cognitive function relative to healthy controls (e.g., processing speed) (p=0.031). A sub-domain measure of working memory (i.e., symbol check; SC) exhibited significant improvement at Weeks 2 and 8 in latency (p= 0.032), SC accuracy (p= 0.046), and objective z-score (p= 0.001) independent of depressive symptoms. A linear regression analysis determined that THINC-it tool measures of processing speed, as well as executive function were significantly associated with changes observed on the pencil and paper version the Digit Symbols Substitution Test (DSST) (p= 0.002) and in Trails Making Test B (TMTB) (p= 0.003), respectively. Conclusion: The THINC-it tool demonstrates sensitivity to change in adults with MDD and is highly correlated with improvements on pencil and paper versions of DSST and TMTB.